Maksimalisasi Penggunaan Metode Profile Matching dalam Menentukan Kandidat Terbaik - Zainal Abidin; Indra Gita Anugrah; Ryco Puji Setyono (Jurnal Informatika Universitas Pamulang, 2019)
Determine the best candidate in a company is something that is natural. There are several methods to determine the best candidate. One of them using the "Profile Matching" method. The method will rate employees from the highest to the lowest value, the assessment is carried out with several aspects of assessment which are categorized into two categories, namely core factors and scondary factors. Core factor is an assessment of the main factors in an assessment and the scondary factor is the supporting factors in an assessment. In weight determining the core factor and scondary factors greatly influence the results of the assessment. With the use of the "Profile Matching" method, it is expected that employee assessment can be maximized and provide results as expected. But in the calculation, there are several factors that are very influential so that the results obtained are unsuitable. Normal calculation using the Profile Matching method with standard values is the middle value produces the best candidate that is not appropriate. Requires modification of the weighting gap table so that the results produced can be maximized and appropriate.